Gambaran Penggunaan Obat pada Pasien Rawat Inap Infark Miokard Akut (IMA) di UPT RSUD Nene Mallomo - Fadilla Syam; Wasliaty Sirajuddin; Ayu Amriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
According to WHO in the 2014 journal, as many as 7.2 million (12.2%) deaths occurred due to Acute Myocardial Infarction. Myocardial infarction is the second leading cause of death in developing countries, with a figure of 2.4 million (9.4%) Americans (Hurulean, 2020). The type of research used is descriptive quantitative research method with a retrospective approach, namely to provide an overview of drug use in Patients with Acute Myocardial Infarction (AMI). A total of 15 medical records and prescriptions for patients with Acute Myocardial Infarction (AMI) were used as samples. The results showed that patients with Acute Myocardial Infarction at UPT RSUD Nene Mallomo for the period June - December 2021 from the data of 15 confirmed patients suffering from Acute Myocardial Infarction, the most used antiplatelet aggregation drugs with a percentage of 37.1 (Aspilet tablets as many as 2, Miniaspi as many as 8, Clopidogrel 75 mg tablets as many as 8 and briclot as many as 8), then anticoagulant drugs with a percentage of 18.5 (Diviti 2.5 mg as many as 13), and antianginal drugs or nitrate with a percentage of 12.8 (ISDN 5 mg tablets for 2, Farsorbid 5 mg tablets for 1, Farsorbid 10 mg tablets for 2, Cedocard 10 mg tablets for 3).